2014
DOI: 10.1182/blood.v124.21.4593.4593
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing of Philadelphia-Negative (Ph-negative) Myeloproliferative Neoplasms (MPNs) and Myelodysplastic/Myeloproliferative Disorders (MDS/MPD)

Abstract: Introduction: The development of next-generation sequencing has made it feasible to interrogate the entire genome or exome (coding genome) in a single experiment. Accordingly, our knowledge of the somatic mutations that cause cancer has increased exponentially in the last years. MPNs and MDS/MPD are chronic myeloid neoplasms characterized by an increased proliferation of one or more hematopoietic cell lineages, and an increased risk of transformation to acute myeloid leukemia (AML). MPNs and MDS/MPDs are heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…DNA was extracted from sorted ECs and tested for the presence of the JAK2 V617F mutation by an allele‐specific polymerase chain reaction (PCR). Data on JAK2 V617F allele burden was extracted from WES results obtained from a cohort of 77 patients with JAK2 V617F ‐positive MPN (including 4 patients with JAK2 V617F MPN‐neg) (Santos et al , ) and from 110 patients previously reported by Nangalia et al ().…”
Section: Demographic Features Of Bcs Patients and Jak2v617f Allele‐bumentioning
confidence: 99%
“…DNA was extracted from sorted ECs and tested for the presence of the JAK2 V617F mutation by an allele‐specific polymerase chain reaction (PCR). Data on JAK2 V617F allele burden was extracted from WES results obtained from a cohort of 77 patients with JAK2 V617F ‐positive MPN (including 4 patients with JAK2 V617F MPN‐neg) (Santos et al , ) and from 110 patients previously reported by Nangalia et al ().…”
Section: Demographic Features Of Bcs Patients and Jak2v617f Allele‐bumentioning
confidence: 99%